PENGARUH VARIABEL MAKRO EKONOMI TERHADAP HARGA SAHAM DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Munthe, Kornel; Harefa, Caisar J (Jurnal Manajemen dan Bisnis, 2020)
The purpose of this study is to influence the effect of exchange rates, interest rates, inflation and Gross Domestic Product on stock prices with profitability as an intervinig variable in manufacturing companies on the Indonesia Stock Exchange. This type of research is explanatory. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange as many as 159 companies with a total sample of 61 companies. The type of data used is secondary data collected by documentation techniques. The results showed that the exchange rate had a negative and significant effect on profitability, SBI interest rates, inflation and Gross Domestic Product partially had a positive and significant effect on profitability, exchange rate variables, SBI interest rates, inflation and Gross Domestic Product simultaneously had a significant effect on profitability, exchange rates and SBI interest rates partially have a negative and significant effect on stock prices, inflation, and Gross Domestic Product and Return on Assets have a positive and significant effect on stock prices, and exchange rate variables, SBI interest rates, inflation, and Domestic Product Gross and profitability simultaneously have an effect and are significant on stock prices.